The Effect of Grapefruit Extracts on Causative Agents of Vaginitis among Women in Babylon Governorate, Iraq - Faleeha Habeeb Hussien; Abeer H. Al-Khafaf; Nada F. Al-Rawi (Medical Journal of Babylon)
Background: Vaginitis is inflammation of the vagina caused by a disruption in the normal vaginal flora. Objectives: This research aims to study the inhibitory activity of raw grapefruit juice, alcoholic, and aqueous grapefruit peel extract against the agents causing vaginitis among women in Babylon Governorate. Materials and Methods: A total of 177 women attending the Gynaecology and Obstetrical Department at Hilla Teaching Hospital in Babylon Governorate were included in the present study. All patients were complaining of vaginitis. The specimens collected in this study were cultured and diagnosed based on microscopic and cultured characteristics and biochemical tests. Also, an antibiotic susceptibility test for some antibiotics was done; aqueous and alcoholic grapefruit (Citrus paradise) peel extracts and juice of grapefruit were used in the study. The antimicrobial activity of both the grapefruit peel extract and raw juice was evaluated against different microorganisms isolated from the high vagina swab of patients presenting with vaginitis. Results: Several vaginitis pathogens were isolated in this study: Staphylococcus aureus was seen to be common, followed by Staphylococcus epidermedis, Escherichia coli, then Enterococcus faecalis, Proteus mirabilis, Klebsiella pneumoniae, Gardnerella vaginalis, Listeria monocytogenes, and Actinomyces spp., In addition, the yeast (Candida albicans) is the second leading cause of vaginitis. Tobramycin is the most effective, while Tetracyclin and Metronidazole had no effect. The inhibitory action of alcoholic grapefruit extract and raw juice is more effective than aqueous extract. Conclusion: The alcoholic grapefruit peel extract and raw grapefruit juice have an inhibitory effect against all agents under study except K. pneumoniae, while the aqueous extract showed less efficacy against the tested microbes.